2022
DOI: 10.1111/tbed.14458
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biological properties of H10N3 avian influenza viruses: A potential pandemic candidate?

Abstract: The continued emergence of human illness caused by avian influenza viruses (AIVs) demonstrates the threat of strains such as H5N1, H7N9, H10N8, and now H10N3. The genetic and biological properties of H10N3 viruses are not fully understood. In this study, three H10N3 strains isolated from live poultry markets (LPMs) were systematically studied. Genome sequencing showed that the poultry‐origin viruses are highly homologous to the human H10N3 isolate. The three avian strains were A/chicken/Jiangsu/0146/2021(abbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 76 publications
2
7
0
Order By: Relevance
“…Liu et al 44 reported that dual receptor‐binding properties were maintained in their two H10N3 isolates bearing HA Q222R and G228S. In Guo's study and ours, all H10N3 viruses with HA Q222R and G228S showed higher affinity for avian‐type receptors than for human‐type receptors, 22 except for one H10N3 isolate (CK/FJ/S1254/2021), which displayed a higher affinity for human‐type receptors in our study (Figure 4G). The existence of H10N3 viruses with increased affinity for human‐type receptors highlights the potential threat of those viruses to humans.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Liu et al 44 reported that dual receptor‐binding properties were maintained in their two H10N3 isolates bearing HA Q222R and G228S. In Guo's study and ours, all H10N3 viruses with HA Q222R and G228S showed higher affinity for avian‐type receptors than for human‐type receptors, 22 except for one H10N3 isolate (CK/FJ/S1254/2021), which displayed a higher affinity for human‐type receptors in our study (Figure 4G). The existence of H10N3 viruses with increased affinity for human‐type receptors highlights the potential threat of those viruses to humans.…”
Section: Discussionsupporting
confidence: 60%
“…Then, in 2021, an H10N3 human case was reported in Jiangsu, China, raising the concern of cross-species transmission of H10 virus. 10,[21][22][23] This case raised questions as to how the H10N3 virus has evolved to infect humans since 2014, and how much risk do H10N3 viruses pose to the poultry industry and public health. To answer these questions, we conducted extensive studies analyzing the genetics, receptor binding properties, replication, and transmissibility of a series of H10N3 viruses isolated in China from 2014 to 2021.…”
mentioning
confidence: 99%
“…The genotype S strain CK-74 induced more severe injury to internal organs compared to the genotype A strain CC-3. The differences in amino acid mutations between the two strains were analyzed, among which nine key mutations, including I 292 V (PB2 protein), K 356 R (PA protein), and I 353 V (NP protein) are associated with increased virulence or replication efficiency (Naffakh et al, 2008;Xu et al, 2016;Guo et al, 2022) (Table 2). These specific amino acid mutations may contribute to the pronounced pathological changes observed in the genotype S isolate.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, isolates derived from wild birds did not manifest these mutations. These genetic alterations may potentially augment viral replication efficiency within host cells by increasing polymerase activity, consequently contributing to increased virulence (Naffakh et al, 2008;Xu et al, 2016;Guo et al, 2022).…”
Section: Key Amino Acid Characterizationmentioning
confidence: 99%
“…As yet, however, there is no evidence of sustained human-to-human transmission, and human infections are unusual. Nevertheless, careful monitoring is crucial in order to promptly identify viral changes and transmission patterns that could make the virus a threat to humans [ 34 , 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%